Attractivity of vinasse spraying to stable flies, Stomoxys calcitrans in a sugarcane area - Taciany F. Souza; Paulo H.D. Cançado; Antonio Thadeu M. Barros (Pesquisa Veterinária Brasileira, 2021)
ABSTRACT: Stable fly (Stomoxys calcitrans) outbreaks have been associated with sugarcane mills in Brazil. This study aimed to evaluate the attractivity of vinasse, a liquid byproduct of ethanol production applied to postharvest sugarcane fields, to adult S. calcitrans. Stable fly abundance was monitored for 21 days in August-September 2014, at a sugarcane mill in the municipality of Nova Alvorada do Sul, state of Mato Grosso do Sul, Brazil. Following mechanized harvesting of sugarcane and the consequent deposition of large amounts of plant residue (straw) in the field, the study area (13.5ha) was surrounded by 22 sticky cylinder (“alsynite”) traps. The area was fertigated with vinasse immediately after the traps were placed. Insects caught in the traps were collected daily at 7:00 a.m., 11:00 a.m. and 15:00 p.m. A total of 83,593 specimens of S. calcitrans were caught, of which 5,516 (6.6%) were attracted within the first five hours after vinasse application. The highest number of S. calcitrans was caught in the first week following vinasse application, with a peak on the 4th day (12,818 flies), which was influenced by adverse weather conditions on the previous days. This study confirms that fertigation of sugarcane fields by spraying vinasse after the harvest attracts S. calcitrans, thus quickly increasing their abundance over the days following application.